Spend less, get more? Explaining health spending and outcome differences between Canada and Italy - Livio Di Matteo; T. P. Barbiero (Review of Economic Analysis (REA), 2020)
Canada spends more than Italy on health per capita and as a share of GDP and has a higher per capita GDP. Yet, life expectancy and infant mortality in Italy are better and have improved more over time. The implication is that the Italian health care system provides better value for money. We examine whether Italy does get better health outcomes at lower costs. Using regression analysis, we find that health spending is determined by similar drivers in both Canada and Italy. We also find that more social spending and health spending in either country do not satisfactorily explain the differences in health outcomes, suggesting the importance of broader socio-economic determinants like income and life-style choices. We conclude that while the levels of per capita health spending in Canada are higher than Italy, this partly reflects historical inertia in Canadian health spending partially attributable to the higher costs of health professionals relative to Italy.
Keywords: I1; I3; F0; H1; N3; 330; health; expenditures; outcomes; Gesundheitskosten; STW-ID; Gesundheitsökonomik; STW-ID; Sterblichkeit; STW-ID; Öffentliche Sozialausgaben; STW-ID; Einkommensverteilung; STW-ID; Vergleich; STW-ID; Italien; STW-ID; Kanada; STW-ID